2011
DOI: 10.3347/kjp.2011.49.1.95
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated with Head Louse Infestation in Korea

Abstract: Head louse infestation (HLI) is one of the most frequently occurring parasitic diseases in children. This study was conducted to investigate the socioeconomic and personal factors influencing HLI in the Republic of Korea. A total of 2,210 questionnaires about various factors related to HLI were obtained from children in 17 primary schools throughout the country. The rate of HLI was significantly lower in children who lived together with mother or in a family where both parents worked. In addition, HLI was lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
16
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 12 publications
7
16
1
Order By: Relevance
“…Similarly, in studies conducted in Korea, Jordan, Egypt, Yemen, Malaysia, and Turkey head lice infestation prevalence was more common among big size families [1517, 19–21]. …”
Section: Discussionmentioning
confidence: 90%
“…Similarly, in studies conducted in Korea, Jordan, Egypt, Yemen, Malaysia, and Turkey head lice infestation prevalence was more common among big size families [1517, 19–21]. …”
Section: Discussionmentioning
confidence: 90%
“…Similar results were found in several studies, while other authors showed contradictory results. 11,12,18,19,28,29 Girls whose mothers washed their hair were less infested than those who washed their own hair. To the best of our knowledge, it is the first time the effect of such a factor on the prevalence of pediculosis is investigated.…”
Section: Discussionmentioning
confidence: 99%
“…30 However found low or no significant correlation between lice infestation and the size of family or the number of people sharing rooms. 12,28 The impact of the socio-economic and education level of parents was investigated. Infestation rate was directly proportional to the father's education level, increasing with higher education (P≤0.01).…”
Section: Discussionmentioning
confidence: 99%
“…Obviously, higher standards of living (higher income, low unemployment rates, better access to water) offer better sanitary security and hygiene and medical care, which is particularly evident in the case of various infectious diseases caused or transmitted by arthropods [4,12,15,18,19,20].…”
Section: Discussionmentioning
confidence: 99%
“…In turn, lice infestation rates were lower in two-parent families with both parents working [15] and in families with few children [24]. Pediculosis usually affects children aged 3-12, who need adults' care [2,4,12,13,21,24].…”
Section: Discussionmentioning
confidence: 99%